1979
DOI: 10.1159/000250743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Benzoyl Peroxide on Skin Surface Lipids

Abstract: Investigations have been performed on the effect of benzoyl peroxide on skin surface lipids by direct lipid extraction with petrol ether and quantitative determination. Though there was no change after 1 week treatment, after 4 weeks a significant reduction of the casual level as well as the replacement sum could be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…Our findings are at variance with those published previously by Fanta and Müller [3]. They reported that when 5% benzoyl peroxide gel was applied to the face of 10 subjects for 4 weeks, the average 'casual' sebum levels de creased by 52% and the 'replacement sum' sebum levels by 55%.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Our findings are at variance with those published previously by Fanta and Müller [3]. They reported that when 5% benzoyl peroxide gel was applied to the face of 10 subjects for 4 weeks, the average 'casual' sebum levels de creased by 52% and the 'replacement sum' sebum levels by 55%.…”
Section: Discussioncontrasting
confidence: 81%
“…More recently, attention has been directed to the possibility that benzoyl per oxide can inhibit sebaceous gland secretion. Studies have been reported to indicate that it lowers surface sebum levels and sebaceous gland mitotic ac tivity in man [3,4] and sebaceous gland size and mitotic activity in ani mals [5].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of treatment and control data of individual subjects showed a de crease of SER in 4 out of 14 patients (pa tients No. 5,6,8,12), whereas a concomit ant SER reduction was observed in both treatment and control areas of 6 patients ( fig. 1).…”
Section: Resultsmentioning
confidence: 83%
“…BPO was reported to produce a primary irritant dermatitis, and patients did not re port an improvement of seborrhea [1,2], In direct methods of assessing sebum pro duction were found to indicate a sebosuppressive effect of BPO [5,8], More estab lished methods for estimating SER also sug gested that BPO exerted a sebosuppressive effect [6] and clinical observations corrobo rated these observations [4], Other studies failed to show that BPO decreases sebaceous gland secretion in acne [10,13,16]. Recent- ly, 5% BPO was reported to increase SER by 22.5% in acne patients after 1 and 2 months of treatment [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation